HAEMONCHUS PLACEI IN CALVES - EFFECTS OF DIETARY-PROTEIN AND MULTIPLE EXPERIMENTAL-INFECTION ON WORM ESTABLISHMENT AND PATHOGENESIS - Gennari, S. M.; Abdalla, A. L.; Vitti, DMSS; Meirelles, C. F.; Lopes, Raimundo Souza [UNESP]; Bressan, MCRV (Elsevier B.V., 1995)
An experiment was conducted to examine the influence of dietary protein and immunisation on parasite establishment and pathogenesis of Haemonchus placei in calves. Four groups of 4-6-month-old worm-free calves (n=4) were given a low protein diet (LP) containing 213 g crude protein (CP) per head per day or a high-protein diet (HP) containing 469 g per head per day CP. Five weeks later, calves in one of the two groups of each dietary treatment were given 50 000 H. placei infective larvae (L(3)). Twenty-five days later, infection in these groups was terminated by dosing with oxfendazole, This immunisation process was repeated 4 days later. Four days after termination of the second immunisation all calves were challenged with 100 000 L(3). Five weeks later, all calves were slaughtered for abomasal worm counts. Worm establishment was lower in the immunised groups; however, only the HP-I group showed a significant reduction (P < 0.05). All calves gained weight during the first 13 week period, and after challenge the non-immunised groups lost weight, independent of the level of protein in the diet (P < 0.05), Packed cell volume values for all treatments only dropped after challenge (P < 0.05) and the HP-immunised group presented values significantly higher when compared with the other treatments, All calves were hypoproteinaemic and hypoalbuminaemic at the end of the experiment, regardless of the treatment. Immunised calves showed a normocytic normochromic anaemia, while the non-immunised groups presented a microcytic normochromic anaemia.
Keywords: HAEMONCHUS PLACEI; CATTLE-NEMATODA; NUTRITION